PROBLEMS OF THE FORMATION OF SOCIO-CULTURAL COMPETENCE OF STUDENTS IN THE STRUCTURE OF THEIR PROFESSIONAL COMPETENCE - Kodirov Umut Roziboyovich (American Journals, 2023)
Our scientific article talks about problems in the formation of students’ professional competence and socio-cultural competence. Socio-cultural competence is an integral characteristic of a person, which is expressed by the presence of tolerance and open attitude towards representatives of different language communities, his theoretical and practical readiness for socio-cultural activities, and a personally conscious positive attitude towards him. It is important to have deep and solid knowledge, skills and experience aimed at effectively solving specific professional tasks in the context of intercultural communication. Socio-cultural competence helps effective intercultural communication, allows to understand the emotional and cognitive characteristics of another nation and prevents the formation of the ideology of national exclusivity. The formation of socio-cultural competence helps to realize one's own value, to understand all aspects of one’s own culture, to compare it with the culture and language of another nation.
Keywords: socio-culturology, professional competence, cultural approach, cognitive function, linguistic approach, communicative activity, multiculturalism, social communication, axiological ability, cultural prism.